1981
DOI: 10.1111/j.1752-0606.1981.tb01404.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics, Implications and Treatment of Extramarital Sexual Relationships for the Family Therapist*

Abstract: This article presents the dynamics, implications and treatment of extramarital sex. Historical and cultural perspectives, various types of infidelity experiences and family therapy implications will be discussed. Marital styles will be outlined as a frame of reference in understanding the topic and the importance of symptom generation vis‐a‐vis infidelity. Finally, specific recommendations for treatment and a brief consideration of extramarital relationships as a healthy alternative marital style will be offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Many previous studies have shown that deficiencies in the primary relationship can play a central role in precipitating and sustaining infidelity [4,15,26,55]. However, not all the available studies have shown an association between extramarital affairs and conflict within the primary couple [45,56–58]. Glass and Wright [55] suggest that primary relationship distress may be important in some cases but not in others.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have shown that deficiencies in the primary relationship can play a central role in precipitating and sustaining infidelity [4,15,26,55]. However, not all the available studies have shown an association between extramarital affairs and conflict within the primary couple [45,56–58]. Glass and Wright [55] suggest that primary relationship distress may be important in some cases but not in others.…”
Section: Discussionmentioning
confidence: 99%
“…They dealt with these issues in isomorphic transactions such as the couple's problems in sharing leisure activities and parenting responsibilities. There was no need to reveal the literal details of the affair to the husband because the problems, of which the affair was only one instance, were dealt with by way of other marital transactions (see also, 5).…”
Section: Family Secretsmentioning
confidence: 99%
“…For example, most authors (cited above) describe as problematic the situation of one spouse confiding an extramarital affair to the marital therapist. But one can view sustained outside relationships as the joint efforts of a couple to triangulate in order to regulate their distance and closeness (5). This pattern would be visible in many of their other interactions affected by the marital dysfunction.…”
Section: Family Secretsmentioning
confidence: 99%
“…Even if no longitudinal studies assessing causal relationship of marital problems and extramarital affairs are available, previous studies have shown that deficiencies in the primary relationship can play a crucial role in precipitating and sustaining infidelity [41,42]. However, not all the available studies have shown an association between extramarital affairs and conflict within the primary couple [43–45]. Glass and Wright [42] suggest that primary relationship distress may be important in some cases, but not in others and that other variables may moderate this association between relationship dissatisfaction and infidelity [46].…”
Section: Discussionmentioning
confidence: 99%